Kebijakan Kontroversial Ibu Kota Nusantara - Mungin Mungin; Iswiyati Rahayu; Irawanto Irawanto (Jurnal Multidisiplin Indonesia, 2026)
The development of the Nusantara Capital City (IKN) in East Kalimantan is a strategic national policy that has sparked controversy because it brings together narratives of development, modernization, and economic equality with ecological and social issues. This study employs a qualitative approach through policy analysis and literature review to examine the government’s narrative construction, ecological impacts, threats to environmental sustainability, and the contradictions between claims of sustainable development and ecological realities. The findings indicate that the IKN development narrative is hegemonic as it emphasizes economic growth, modernization, and the Indonesia 2045 Vision, yet it lacks public participation and fails to adequately address the critiques of indigenous communities and environmental experts. IKN development also has the potential to cause systemic ecological impacts, such as deforestation, the loss of endemic wildlife habitats, increased carbon emissions from peatland conversion, and heightened risks of flooding and forest fires. Furthermore, IKN development policies threaten environmental sustainability as they are not yet fully grounded in ecological carrying capacity assessments and the protection of vulnerable areas. This study employs a qualitative approach through policy analysis and a literature review to examine the construction of the government’s narrative and its ecological impacts. The study concludes that there is a contradiction between the claim that the IKN is a sustainable city and development practices that are potentially exploitative. Therefore, development governance that is transparent, participatory, accountable, and based on ecological sustainability is required.z